Changing epidemiology and trends in incidence of kidney cancer in England, 1985-2019: Anjum Memon. (25th October 2022) - Salari, Y; Bannister, P; Memon, A
Abstract: Background: Kidney cancer is the 7th most common cancer in the UK, accounting for 4% of all new cancer cases. The risk factors for kidney cancer include obesity, smoking, hypertension, and exposure to certain environmental and occupational carcinogens. We conducted a retrospective population-based cohort study to examine whether there have been changes in the incidence of kidney cancer in England during the past four decades. Methods: Individual level data for patients diagnosed with kidney cancer in England during 1985-2019 were obtained from the Office for National Statistics/Public Health England. Average annual incidence rates were calculated by two age categories (0-49, 50+ years) and all ages combined during the seven five-year time periods (1985-89 to 2015-19). The percentage change in incidence was calculated as change in the average annual incidence rate from the first (1985-89) to the last time period (2015-19). Results: During the 35-year study period, a total of 197, 819 new cases of kidney cancer were registered in England (62.4% males, 37.6% females). In young people aged 0-49 years, the average annual incidence rates increased by 164% in males and 144% in females (from 1.4/100, 000 in 1985-89 to 3.7/100, 000 in 2015-19 in males and from 0.9/100, 000 in 1985-89 to 2.2/100, 000 in 2015-19 in females). In older people aged 50+ years, the rates increased by 129% in males and 147% in females (from 24.5/100, 000 in 1985-89 to 56.0/100, 000 in 2015-19 in males and from 11.9/100, 000 in 1985-89 to 29.4/100, 000 in 2015-19 in females). Conclusions: There has been a steady and significant increase in the incidence of kidney cancer in England over the past four decades. The largest increase (164%) was observed in young males aged 0-49 years, which was unexpected. Considering the risk factors for kidney cancer, further research is needed to understand the role of environmental/occupational exposures in causing kidney cancer. Key messages: About 24% of kidney cancers in the UK are attributed to obesity and 13% to smoking. This research highlights the benefits of reducing the prevalence of obesity and smoking in the general population. The unexpected significant increase in the incidence of kidney cancer in young people aged 0-49 years needs further investigation.